2004
DOI: 10.1093/logcom/14.6.857
|View full text |Cite
|
Sign up to set email alerts
|

The Expressiveness of Spider Diagrams

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…The language of spider diagrams is also accompanied by inference rules, which results in the logic of spider diagrams. This logic is expressively equivalent to monadic first-order logic with equality (MFOLE) [23]. We also developed a new set of sound inference rules, which represent an extensions of the system in [12] and prove them to be complete -for details, see Section 3.…”
Section: Spider Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…The language of spider diagrams is also accompanied by inference rules, which results in the logic of spider diagrams. This logic is expressively equivalent to monadic first-order logic with equality (MFOLE) [23]. We also developed a new set of sound inference rules, which represent an extensions of the system in [12] and prove them to be complete -for details, see Section 3.…”
Section: Spider Diagramsmentioning
confidence: 99%
“…Note that the connectives ←→, −→, and ¬ were excluded from the sound and complete spider diagram logic studied by Stapleton et al [23]. In Fig.…”
Section: Syntaxmentioning
confidence: 99%
“…It has also been shown that spider diagrams are equivalent to MFOL with equality [10]; MFOL [=] extends MFOL by including =, allowing one to assert the distinctness of elements. To establish the expressiveness of spider diagrams, a different approach to that of Shin's for Venn-II was utilized.…”
Section: Introductionmentioning
confidence: 99%
“…From [16] we know that spider diagrams without order are expressively equivalent to monadic first order with equality, denoted M F oL [=]. Our extension to spider diagrams adds an order relation to the semantic models.…”
Section: Comparing Classes Of Regular Languages and Spider Diagramsmentioning
confidence: 99%